Death registration in Nigeria: a systematic literature review of its performance and challenges - Olusesan Ayodeji Makinde; Clifford Obby Odimegwu; Mojisola O. Udoh; Sunday A. Adedini; Joshua O. Akinyemi; Akinyemi Atobatele; Opeyemi Fadeyibi; Fatima Abdulaziz Sule; Stella Babalola; Nosakhare Orobaton (Taylor & Francis Group, 2020)
Background Death registration provides an opportunity for the legal documentation of death of persons. Documentation of deaths has several implications including its use in the recovery of inheritance and insurance benefits. It is also an important input for construction of life tables which are crucial for national planning. However, the registration of deaths is poor in several countries including Nigeria. Objective This paper describes the performance of death registration in Nigeria and factors that may affect its performance. Methods We conducted a systematic literature review of death registration completeness in Nigeria to identify, characterize issues as well as challenges associated with realizing completeness in death registration. Results Only 13.5% of deaths in Nigeria were registered in 2007 which regressed to 10% in 2017. There was no data reported for Nigeria in the World Health Organization database between 2008 and 2017. The country scored less than 0.1 (out of a maximum of 1) on the Vital Statistics Performance Index. There are multiple institutions with parallel constitutional and legal responsibilities for death registration in Nigeria including the National Population Commission, National Identity Management Commission and Local Government Authorities, which may be contributing to its overall poor performance. Conclusions We offer proposals to substantially improve death registration completeness in Nigeria including the streamlining and merger of the National Population Commission and the National Identity Management Commission into one commission, the revision of the legal mandate of the new agency to mainly coordination and establishment of standards. We recommend that Local Government authorities maintain the local registries given their proximity to households. This arrangement will be enhanced by increased utilization of information and communications technology in Civil Registration and Vital Statistics processes that ensure records are properly archived.